Competencias comunicativas eficaces mediante estrategías de aprendizaje cooperativo - García Gonzáles, Alfonso (2014)
Cooperative learning is one of the main medicines in education: the student takes an active role in their own learning process. Methodological issues are very important within university, since the development project of the European Higher Education Area proposes very profound changes in the educational paradigm, changes in the role of teachers and students inside and outside the classroom. To give force to this argument, the implementation of Cooperative Learning Questionnaire Arellano, Navarro and Sosa (2007) was taken to 692 students enrolled in first grade of primary education in 2010-2011. The sample coincides with the universe of freshmen in the Bachelor of Primary Education, comprising 87% of women with a mean age of 19 years, which yielded an index of 0.83 for internal consistency of the instrument. The results point to the importance of strengthening cooperative learning in university classrooms, given that there are few occasions when they can put into play.